Visual programming with Interaction Nets - Hassan, Abubakar (2008)
Programming directly with diagrams offers potential advantages such as visual intuitions, identification of errors (debugging), and insight into the dynamics of the algorithm. The purpose of this paper is to put forward one particular graphical formalism, interaction nets, as a candidate for visual programming which has not only all the desired properties that one would expect, but also has other benefits as a language, for instance sharing computation.